Расчёт ЭДС возбуждения бесконтактной явнополюсной синхронной машины с переменной структурой обмотки ротора - Клементьев, Александр Васильевич (НТУ "ХПИ", 2005)
Предложены формулы, связывающие ток обмотки возбуждения возбудителя и ЭДС возбуждения обмотки статора бесконтактной явнополюсной совмещённой синхронной машины с переменной структурой обмотки ротора.

Expressions relating excitation winding current to excitation electromotive force of the stator winding of a noncontact combined salient-pole synchronous machine with a variable-structure rotor winding are given.
Calculation of excitation electromotive force of a noncontact salient-pole synchronous machine with a variable-structure rotor winding
Keywords: обмотки ротора; электрические машины; синхронные машины; электрические аппараты; variable-structure rotor winding; noncontact salient-pole; excitation electromotive force; synchronous machine